Harsh environments, life history strategies, and adjustment: A longitudinal study of Oregon youth. (January 2016) - Hampson, Sarah E.; Andrews, Judy A.; Barckley, Maureen; Gerrard, Meg; Gibbons, Frederick X.
Abstract: We modeled the effects of harsh environments in childhood on adjustment in early emerging adulthood, through parenting style and the development of fast Life History Strategies (LHS; risky beliefs and behaviors) in adolescence. Participants were from the Oregon Youth Substance Use Project (N = 988; 85.7% White). Five cohorts of children in Grades 1–5 at recruitment were assessed through one-year post high school. Greater environmental harshness (neighborhood quality and family poverty) in Grades 1–6 predicted less parental investment at Grade 8. This parenting style was related to the development of fast LHS (favorable beliefs about substance users and willingness to use substances at Grade 9, and engagement in substance use and risky sexual behavior assessed across Grades 10–12). The indirect path from harsh environment through parenting and LHS to (less) psychological adjustment (indicated by lower life satisfaction, self-rated health, trait sociability, and higher depression) was significant (indirect effect −.024, p  = .011, 95% CI = −.043, −.006). This chain of development was comparable to that found byGibbons et al. (2012) for an African-American sample that, unlike the present study, included perceived racial discrimination in the assessment of harsh environment. Highlights: Evolutionary development theory and the prototype willingness model framed this study. Harsh environments in childhood impacted adjustment one-year post high school. Parental investment and fast life history strategies in adolescence were mediators. These findings for White working class youth were comparable to a previous study of Black youth.